Association Between Media Doses of the Tips From Former Smokers Campaign and Cessation Behaviors and Intentions to Quit Among Cigarette Smokers, 2012-2015. (February 2018) - Davis, Kevin C.; Patel, Deesha; Shafer, Paul; Duke, Jennifer; Glover-Kudon, Rebecca; Ridgeway, William; Cox, Shanna
Background . Since 2012, the Centers for Disease Control and Prevention (CDC) has implemented Tips From Former Smokers ( Tips ), the first federally funded tobacco education campaign in the United States. To date, there are no evaluations of its long-term impact. Aims. To assess the impact of varied doses of the Tips campaign from 2012 through 2015 on cessation-related behaviors and intentions among U.S. smokers. Method. We used a national probability-based online survey of cigarette smokers ( n = 22, 189) and recent quitters ( n = 776) to examine associations between doses of Tip s advertising, measured by gross rating points (GRPs), and intentions to quit smoking in the next 30 days and quit attempts within the past 3 months. A curvilinear (i.e., square root) functional form of GRPs was used to capture patterns of diminishing effects at higher GRP levels. Results. An increase of 1, 000 quarterly Tips GRPs at the media market level was associated with increased odds of making a quit attempt in the past 3 months (adjusted odds ratio = 1.23, p < .001) and increased odds of intending to quit in the next 30 days (adjusted odds ratio = 1.17, p = .030). Discussion. Results suggest that CDC-recommended media buys of 800 to 1, 000 GRPs per quarter are sufficient to generate statistically significant increases in the likelihood of quit attempts in the past quarter. Conclusions. The Tips campaign has had a substantial impact on cessation behaviors among U.S. adult smokers over time. These data support the continued use of graphic and/or emotional media campaigns that encourage smokers to quit to further reduce tobacco use in the United States.